Financial Development, Institutional Quality and Economic Growth: Evidence from ECOWAS Countries - Appiah, Michael; Li, Fanglin; Frowne, Doreen Idan (Organizations and Markets in Emerging Economies, 2020)
Most of the literature that explored the relationship between financial development and economic growth taking into consideration the roles played by institutional quality in the ECOWAS region still debates on the roles of institutional quality on economic growth. This study used data from 1996-2017 for 15 emerging economies within the ECOWAS by applying two-step SYS GMM (SGMM) estimators. The following conclusions were developed: first, the study discovered that financial development has no significant and positive impact on economic growth in the ECOWAS region. Secondly, regulatory quality and control of corruption, which are considered as institutional quality variables, have opposing results with control of corruption reducing growth as well as regulatory quality variable increasing growth. Again, the results indicate that capital formation has a positive association with growth and labor force influencing growth negatively. Finally, due to a lack of proper corruption control systems in the region and poor financial sector development, growth cannot improve.
Keywords: financial development; economic growth; institutional quality; system GMM; emerging countries